Richard Flury the life and music of a Swiss romantic - Walton, Chris 1963- (Toccata Press, 2017)
The late-Romantic composer Richard Flury (1896-1967) was born in Biberist, a tiny town outside the Baroque city of Solothurn in northern Switzerland. He went to school in Solothurn, later taught there, conducted its orchestra, and had his operas and ballets performed at the local theatre by its semi-professional ensemble. But Flury was more than just another conservative composer stuck in the provinces. His teachers included Ernst Kurth and Joseph Marx of Vienna, and his music was performed by conductors such as Felix Weingartner and Hermann Scherchen and star instrumentalists like Wilhelm Backhaus and Georg Kulenkampff. His first opera was conducted by a former student of Berg and Schoenberg who became his staunch advocate, and during the Second World War Flury worked closely with several Jewish emigre writers and musicians from Germany and Czechoslovakia.In his music of the early 1930s, the influence of Berg and Hindemith became apparent as Flury dabbled in modernism and free tonality before moving back to a more traditionalist stance; but he was also a fine tunesmith who loved writing Viennese waltzes and violin miniatures after the manner of Kreisler. In both his aesthetic and his career, Flury offers a fascinating case of a man negotiating constantly between the centre and the periphery - and composing some very good music in the process.The book includes a 23 track CD of Flury's music
Keywords: Flury, Richard -- 1896-1967; Geschichte 1896-1967; Dirigent; Komponist; Schweiz; Biografie; Werkverzeichnis; CD